Institutional change and regional development in China: the case of commodity trading markets - Wang, Jinming; Gooderham, Paul (SAGE Publications, 2013)
With this paper we explore how institutional changes have influenced the regional development of Yiwu City, East China. The regional development in Yiwu City can be regarded as constituting a specific model in transitional China, which revolves around the establishment, growth, and internationalization of the local commodity trading market. The success of the Yiwu model lies in the interaction between globalization, local institutions, and commodity trading markets. However, we argue that the strategic coupling perspective has its limitations in explaining the development trajectory of the Yiwu model. We develop an integrated paradigm of regional development located between new regionalism and global production networks by synthesizing Scott’s institutional framework. We identify a pronounced and long-established cultural–cognitive element in the entrepreneurial spirit of local people, which led to the establishment of a commodity trading market at the beginning of 1980s. However, the sustainable development of the Yiwu model needs to be supplemented by normative and regulative institutional pillars. We further argue that the developmental local state remains critical to the regional development in developing countries in terms of correcting market failure, encouraging entrepreneurship, and creating a competitive business environment to accommodate globalization.